Pro WordPress Theme Development - Onishi, Adam.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2013)
Pro WordPress Theme Development is your comprehensive guide to creating advanced WordPress themes. Designed for for professional web designers and developers who are comfortable with PHP and WordPress, this book teaches you every aspect of professional theme development. You will learn how to build themes from scratch, how to monetize the themes you create, and how to capitalize on this by creating advanced themes for your clients or selling premium themes. This book builds on your current knowledge of PHP and web development to create a WordPress theme from scratch. It uses a real-world theme example that you can build, to demonstrate each feature in a practical way. It shows you how to take control of WordPress with custom posts types and taxonomies, and covers anatomy and hierarchy, use of the loop, hooks, short codes, plug-ins and much more. WordPress is one of the most successful open-source blogging and content management systems available, and theme development has become a major part of the WordPress ecosystem. Start working with WordPress themes like a pro today with Pro WordPress Theme Development.
Keywords: Computer science; Computer Science; Computer Science, general